Waste management knowledge, its production, recontextualisation and circulation in Expanded Public Works Programme (EPWP) training programmes - Giqwa, Nomfundiso Louisa (Rhodes University, Faculty of Education, Department of Education, 2018)
This study set out to investigate the structuring, recontextualisation and circulation of waste management knowledge in the South African environmental Expanded Public Works Programme (EPWP) Waste Management Projects. In this thesis these projects also referred to as the Working on Waste (WoW) programme or focus area within the Environmental Protection and Infrastructure Programme (EPIP) hosted by the National Department of Environmental Affairs. Expanded Public Work Programmes are a strategy used by governments to address unemployment and in South Africa; the programmes also seek to address a need for skills development. In this study, the focus is on EPWP waste management knowledge, training programmes and activities only. With waste management knowledge as the core interest, the focus of the investigation was on knowledge circulation of waste management via informal (participation in the project) and formal training of workers at Level 2 National Qualifications Framework (NQF). The study started by firstly investigating what waste management knowledge is produced in the Field of Production via scientific research and policy. It then studied how this waste management knowledge is recontextualised into qualifications and skills programmes designed in the official recontextualising field and learning materials and training programmes designed and offered in the professional recontextualising field. The study also focused on the knowledge of workers and their experience of training in the EPWP workplaces, with an emphasis on rural workplaces. This is where the Department of Environmental Affairs (DEA) is placing emphasis on training for job creation, empowerment and skills development, and it is also where a number of EPWP Working on Waste programmes are being implemented. The aim was also to develop an understanding of how knowledge circulates amongst learners in training sessions and in workplaces. To do this, I drew on Bernstein's theory of the pedagogical device which provides theoretical lenses and a language of description to explain how knowledge is recontextualised from the field of production to the field of reproduction. To investigate the structuring of this knowledge by official and pedagogical recontextualisers, I drew on the work of Maton, who offers a Legitimation Code Theory to explain the principles structuring knowledge, of which I used specialisation and semantics (two of his suite of knowledge structuring principles) for analysis. The questions that guided the study throughout were: 1. What is the structure of legitimate knowledge and knowers in waste management? 2. What are the underlying principles underpinning knowledge and knowers in waste management? 3. How is the knowledge recontextualised in waste management training qualifications, documents and manuals for worker training at NQF Level 2? 4. How is the knowledge reproduced and evaluated in the waste management EPWP training activities (formal) and workplaces (informal)? 5. How does waste management knowledge circulate amongst the workers in the EPWP training activities and workplaces? For this study I used the case study method, focusing only on one field or DEA EPWP focus area (waste management) and one programme (EPWP Working on Waste), looking in more depth at two cases (two similar types of projects) within the EPWP Working on Waste programme, though they are situated in different areas and though I could only carry through observations of actual workplace training in one of the two sites due to contextual circumstances. The first project was situated in the Amathole District Municipality while the second one was situated in the Chris Hani District Municipality, both of which are in the rural towns of the former Transkei region in the Eastern Cape, South Africa. This area has been at the forefront in accessing funding for these projects due to the level of poverty surrounding these towns and the inability of the local government sphere to deliver on its mandate in the region. Data was collected through document analysis, questionnaires, interviews and observations. Documents analysed were research documents produced by researchers at the level of production as well as legal frameworks guiding waste management processes in this country. Qualifications and Unit Standards at Level 2, as well as training materials designed by providers were analysed. Training in one of the projects was observed and workers in both sites were interviewed twice. The main finding of the study is that waste management knowledge is characterised by interdisciplinarity and a strong epistemic relation which emphasises procedural and technical forms of knowledge. The study found that the knowledge constructed in the field, as well as the policies, qualifications and training programmes are all consequently characterised by a strong epistemic code (ER+) and a weak social relations code (SR-). The study also identified a 'code clash' with the knowledge of workers in rural towns whose knowledge and experience of waste management was found to reflect a strong social relation (SR+) and weak epistemic code (ER-), a pattern which was traced back to a similar code in waste management knowledge at home and school (i.e. workers' prior knowledge and learning experiences). This created difficulties for the trainers who sought to use strategies of descending from the abstract to the concrete in various 'descending' semantic waves that tended to move from high levels of semantic density (SD+) to lower levels of semantic density (SD-) as the training provider sought to contextualise a range of concepts. This was the main strategy identified for mediating waste management knowledge reflecting a dominant pattern of SD+/SG- to SD-/SG+ (with SG meaning semantic gravity). This shows that the trainer seldom started mediating concepts from the basis of workers' prior knowledge and experience and observations showed little responsiveness from workers resulting from this strategy. Despite this, the study found that workers did develop an improved understanding of specialised waste management knowledge over time, especially through observing and doing more complex tasks in the workplace. The study offers a model for addressing the pedagogical difficulty identified around the code clash, and suggests that further attention needs to be given to 'ascending' from the concrete to the abstract in pedagogical practices. The study also pointed to the need for a more inclusive knowledge framework for waste management training, especially in the field of recontextualisation (both the official and pedagogical recontextualisation fields) to extend possibilities for workers to learn more about economic potential and access routes into more sustainable jobs. It identifies the need for a more systemic approach to waste management in rural towns and municipalities, improved compliance and also proposes that better waste management practices are modelled to avoid performative contradictions between the knowledge promoted in the field of production and the official and pedagogical recontextualising fields and the field of reproduction, where workers are learning this knowledge via a mix of accredited training and exposure to participation in waste management practices. This study contributes to new knowledge in that it offers an epistemically grounded and theorised pedagogical process model for Level 2 Waste Management Training (in the EPWP programmes, but potentially also more broadly) that accords with the need for a strong epistemic relation code (ER+) embodied in the need for learning scientific and technical waste management knowledge and procedures. It also addresses workers' needs for greater epistemic access and participation in knowledge building and application of waste management knowledge in praxis as per the purpose of the EPW training programmes, thereby potentially opening up more sustainable learning pathways for them out of poverty through the EPWP training opportunities. The study has pointed to key areas for further research, including further research on the proposed model, further research into Level 2 pedagogical practices and further research into the foundations of waste management learning in schools. Most of the workers who were participating in the training in the EPWP programmes were educated at above Level 2 before participating in the projects, yet their knowledge and experience of waste management was mostly based on everyday knowledge, pointing to an absence of adequate waste management education in schools in rural contexts in South Africa. The study has also made various recommendations for improving waste management education and training at Level 2 in EPWP programmes in rural areas in particular (but potentially also more widely), notably the need to develop a more inclusive knowledge framework that includes historical and economic knowledge more explicitly at all levels of the recontextualisation process; improved pedagogical and assessment practices that take better account of learners knowledge and experiences in knowledge building processes; and giving attention to structural and systemic approaches to waste management in rural areas to avoid performative contradictions that arise between the knowledge being promoted in the field of production and the field of reproduction and the actual context of waste management.
Keywords: Refuse and refuse disposal -- South Africa -- Eastern Cape; South Africa. Expanded Public Works Programme; Refuse and refuse disposal -- Employees -- Training of -- South Africa -- Eastern Cape; South Africa. Department of Environmental Affairs; Knowledge, Theory of; Knowledge, Sociology of